SPE Western North American and Rocky Mountain Joint Meeting 2014
DOI: 10.2118/169541-ms
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Stimulated Rock Volume from Microseismic Pointsets to Production Data - A Horn River Case Study

Abstract: Hydraulic fracture monitoring from microseismic allows operators to optimize completions through a clear understanding and correlation of the reservoir response to stimulation. Furthermore it helps operators to improve production and avoid out of zone growth by identifying patterns of fluid movement, fracture growth and connectivity. These critical insights allow refinements to the treatment plan, and provide useful insights for long-term improvements regarding well spacing, well design, and completion design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Jones et al (2013) and Chen et al (2016) showed that the complexity and connectivity of the fracture network have great influences on production, implying that the bi-wing fracture model is not fit for the simulation of a complex fracture network. Otherwise, it is found that the critical zone of the stimulated volume is always smaller than the area obtained by the microseismic monitoring (Friedrich and Milliken 2013;Rahimi Zeynal et al 2014). These problems motivate the development of a fracture model that is multileveled and easily adjusted.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Jones et al (2013) and Chen et al (2016) showed that the complexity and connectivity of the fracture network have great influences on production, implying that the bi-wing fracture model is not fit for the simulation of a complex fracture network. Otherwise, it is found that the critical zone of the stimulated volume is always smaller than the area obtained by the microseismic monitoring (Friedrich and Milliken 2013;Rahimi Zeynal et al 2014). These problems motivate the development of a fracture model that is multileveled and easily adjusted.…”
Section: Introductionmentioning
confidence: 78%
“…According to the reservoir simulation, the well performance should be higher if the overall stimulated reservoir area is regarded as being filled with a high conductivity fracture network, so the real contribution of the networks is overestimated. Rahimi Zeynal et al (2014) proposed that the contributing stimulated volume is relatively smaller than that of the microseismic monitored through rate-transient analysis. The effective proppant volume (EPV) is different from the SRV (Friedrich and Milliken 2013).…”
Section: Crv Calibrationmentioning
confidence: 99%
“…A similar evaluation in horizontal wells is much more difficult because of the complexities of the completion and stimulation. Numerous studies of hydraulic fractures in horizontal wells have resulted in very complex distribution of microseismicity in shale reservoirs (e.g., Maxwell et al 2002;Daniels et al 2007;Waters et al 2009a;Ciezobka and Salehi 2013;Suliman et al 2013;Zeynal et al 2014;Virues et al 2015, etc. ), but none of these had ancillary data that actually validated the generation of a complex network.…”
Section: Fracture Complexitymentioning
confidence: 99%
“…Considerable effort has been expended to construct DFNs from microseismic data (e.g., Mayerhofer et al 2006;Jacot et al 2010;Eisner et al 2010;Cipolla et al 2011a;Neuhaus et al 2012Neuhaus et al , 2013Zeynal et al 2014;Cipolla and Wallace 2014;Yu et al 2015, etc. ) and use them for engineering purposes-either modeling the stimulation, production, or both.…”
Section: Dfnmentioning
confidence: 99%
“…Clearly, the shale gas production behavior strongly correlates with the SRV. 12,14 The associated models are proposed based on the concept of the SRV. The analytical models for single gas flow were first proposed based on linear flow assumption.…”
Section: Introductionmentioning
confidence: 99%